Comment « donner forme » à des connaissances sensorielles en contexte de formation? Analyse des interactions lors d’une séance de formation en entreprise - Sylvie Grosjean (Communiquer)
In this paper, we explain how materiality, corporeality and language play a key role in the constitution of “sensible knowledge” in organization. More specifically, we are interested in the communicational processes supporting the constitution of sensible knowledge. The “shaping” of sensible knowledge raises particularly pertinent questions to communication scholars because the sensory experiences in work situations are difficult to formalize and to pass on. Our study focuses on “multimodal resources” (discursive, material and involving the body) through which “sensible knowledge” is generated, shaped and shared in context of professional training. Our analysis is based on a multimodal analysis of interaction and the empirical situation analyzed in this text is a training session that was attended by an intern and a senior consultant in hydrogeology.